2011
DOI: 10.4236/jmp.2011.24035
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Supercurrent Transistors in Silicon Quantum Wells Confined by Superconductor Barriers

Abstract: We present the findings of spin-dependent single-hole and pair-hole transport in plane and across the p-type high mobility silicon quantum wells (Si-QW), 2 nm, confined by the superconductor δ-barriers on the n-type Si (100) surface. The oscillations of the conductance in normal state and the zero-resistance supercurrent in superconductor state as a function of the top gate voltage are found to be correlated by on-and off-resonance tuning the two-dimensional levels of holes in Si-QW with the Fermi energy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The negative-U pairing and the reconstruction of shallow acceptors into the trigonal dipole centers are accompanied by a formation of the correlation gap in the boron acceptor band [3,9]. The correlation gap distorts the density of states (DOS) which became different from its ordinary parabolic law.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The negative-U pairing and the reconstruction of shallow acceptors into the trigonal dipole centers are accompanied by a formation of the correlation gap in the boron acceptor band [3,9]. The correlation gap distorts the density of states (DOS) which became different from its ordinary parabolic law.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously found that the shallow boron acceptors under high concentration demonstrate the negative-U properties and can reconstruct into the dipole centers [1,2]. In the present work we study the heavily boron doped nanoscale silicon p + -n junctions which have been shown to represent the p-type silicon quantum well (Si-QW) confined by wide-band-gap heterobarriers on the Si (100) wafer [3]. The high concentration of boron, 5 × 10 21 cm -3 , in the heterobarriers is essentially higher than the critical concentration of the Mott transition [4] which seems have to cause a metallic-like conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many researches into SiOC films, because it is necessary to develop low dielectric (low-k) constant materials, as alternative to silicon dioxide film. Lowk SiOC film as interlayer dielectric material (ILD) has been used for the gate dielectric materials in FET (field effect transistor) devices, or as an insulator for passivation in solar cells [6][7][8][9]. The SiOC film was made by chemical vapor deposition (CVD) and spin on coating deposition (SOD), but there are some differences between the origins of the decreasing dielectric constant.…”
Section: Introductionmentioning
confidence: 99%